Rate of Memory Change Before and After Cancer Diagnosis - Ospina-Romero, Monica; Abdiwahab, Ekland; Kobayashi, Lindsay; Filshtein, Teresa; Brenowitz, Willa D; Mayeda, Elizabeth R; Glymour, M. Maria (JAMA Network Open, 2019)
IMPORTANCE: Patients with a history of cancer, even nonfatal cancers, have lower subsequent Alzheimer disease incidence. An inverse biological link between carcinogenesis and neurodegeneration has been hypothesized, although survival and detection biases are possible explanations. OBJECTIVE: To compare long-term memory trajectories before and after incident cancer with memory trajectories of similarly aged individuals not diagnosed with cancer. DESIGN, SETTING, AND PARTICIPANTS: This population-based cohort study included 14 583 US adults born before 1949 with no cancer history from the Health and Retirement Study. Biennial assessments were performed for up to 16 years from 1998 to 2014. Data analysis was performed from January 8 to October 5, 2018. EXPOSURES: Self-reported physician diagnosis of any cancer (excluding nonmelanoma skin cancer) during follow-up. MAIN OUTCOMES AND MEASURES: A composite memory score standardized to a mean (SD) of 0 (1) at baseline was based on immediate and delayed word-list recall and proxy assessments. The rate of memory change among people diagnosed with cancer during follow-up before and after diagnosis was compared with rate of memory change in individuals who remained cancer free during follow-up using linear mixed-effect models with random intercepts and slopes. RESULTS: A total of 14 583 participants were included in the sample (mean [SD] age, 66.4 [10.4] years; 8453 [58.0%] female). The mean (SD) follow-up was 11.5 (5.1) years; 2250 had a cancer diagnosis during follow-up, and 12 333 had no cancer diagnosis during follow-up. The rate of memory decline in the decade before a cancer diagnosis was 10.5% (95% CI, 6.2%-14.9%), which was slower than memory decline in similarly aged cancer-free individuals. For individuals diagnosed at 75 years of age, mean memory function immediately before diagnosis was 0.096 SD units (95% CI, 0.060-0.133 SD units) higher compared with that among similarly aged cancer-free individuals. A new cancer diagnosis was associated with a short-term decline in memory of −0.058 (95% CI, −0.084 to −0.032) SD units compared with memory before diagnosis. After diagnosis, the rate of memory decline was 3.9% (95% CI, 0.9%-6.9%) slower in individuals with cancer than in those without a cancer diagnosis. CONCLUSIONS AND RELEVANCE: In this study, older individuals who developed cancer had better memory and slower memory decline than did similarly aged individuals who remained cancer free. These findings support the possibility of a common pathologic process working in opposite directions in cancer and Alzheimer disease.